Degradability of hexachlorocyclohexanes in water using ferrate (VI) - Homolková, M; Hrabák, P; Kolář, M; Černík, M (Water science and technology, 2015)
Regarding environmental pollution, the greatest public and scientific concern is aimed at the pollutants listed under the Stockholm Convention. These pollutants are not only persistent but also highly toxic with a high bioaccumulation potential. One of these pollutants, γ-hexachlorocyclohexane (γ-HCH), has been widely used in agriculture, which has resulted in wide dispersion in the environment. Remediation of this persistent and hazardous pollutant is difficult and remains unresolved. Of the many different approaches tested, to date, none has used ferrates. This is unexpected as ferrates are generally believed to be an ideal chemical reagent for water treatment due to their strong oxidation potential and the absence of harmful by-products. In this paper, the degradation/transformation of HCHs by ferrates under laboratory conditions was studied. HCH was degraded during this reaction, producing trichlorobenzenes and pentachlorocyclohexenes as by-products. A detailed investigation of pH conditions during Fe(VI) application identified pH as the main factor affecting degradation. We conclude that ferrate itself is unreactive with HCH and that high pH values, produced by K₂O impurity and the reaction of ferrate with water, are responsible for HCH transformation. Finally, a comparison of Fe(VI) with Fe(0) is provided in order to suggest their environmental applicability for HCH degradation.
Keywords: hexachlorcyklohexan; Iron; insekticidy; oxidace-redukce; Insecticides; voda; Water Pollutants, Chemical; Water Purification; železo; Hydrogen-Ion Concentration; Water; Oxidation-Reduction; chemické látky znečišťující vodu; čištění vody; koncentrace vodíkových iontů; Hexachlorocyclohexane